2020
DOI: 10.1002/glia.23816
|View full text |Cite
|
Sign up to set email alerts
|

Toxoplasma infection induces microglia‐neuron contact and the loss of perisomatic inhibitory synapses

Abstract: Infection and inflammation within the brain induces changes in neuronal connectivity and function. The intracellular protozoan parasite, Toxoplasma gondii, is one pathogen that infects the brain and can cause encephalitis and seizures. Persistent infection by this parasite is also associated with behavioral alterations and an increased risk for developing psychiatric illness, including schizophrenia. Current evidence from studies in humans and mouse models suggest that both seizures and schizophrenia result fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 126 publications
(164 reference statements)
1
38
0
Order By: Relevance
“…During development, microglial prune numerous extra excitatory presynaptic terminals to sculpt postnatal neural circuits (Mosser et al, 2017;Schafer et al, 2012;Zhan et al, 2014). Apart from synapse pruning, microglia also displace presynapses surrounding neuronal soma under experimental conditions that mimic neuroinflammation or a transection of the mouse facial nerve (Blinzinger and Kreutzberg, 1968;Carrillo et al, 2020;Chen et al, 2014;Trapp et al, 2007); however, knowledge of the presence and contribution of such actions of microglia on neurological disorders is still lacking.…”
Section: Microglial Displacement Of Presynapses Is a Uniformmentioning
confidence: 99%
“…During development, microglial prune numerous extra excitatory presynaptic terminals to sculpt postnatal neural circuits (Mosser et al, 2017;Schafer et al, 2012;Zhan et al, 2014). Apart from synapse pruning, microglia also displace presynapses surrounding neuronal soma under experimental conditions that mimic neuroinflammation or a transection of the mouse facial nerve (Blinzinger and Kreutzberg, 1968;Carrillo et al, 2020;Chen et al, 2014;Trapp et al, 2007); however, knowledge of the presence and contribution of such actions of microglia on neurological disorders is still lacking.…”
Section: Microglial Displacement Of Presynapses Is a Uniformmentioning
confidence: 99%
“…Given that prior work suggested that Toxoplasma infection might specifically affect inhibitory neurons ( Brooks et al, 2015 ), we first examined how often TINs co-localized with two common markers for inhibitory interneurons, calbindin and parvalbumin. We chose these makers rather than the pan-inhibitory marker glutamate decarboxylase (GAD) [GAD + interneurons make up approximately 15–20% of all cortical neurons ( Gentet et al, 2000 ; Lodato and Arlotta, 2015 )] as GAD staining is altered in Toxoplasma- infected brain ( Brooks et al, 2015 ; Carrillo et al, 2020 ). Fortunately, parvalbumin labels 40–50% of GAD + interneurons and calbindin labels approximately 30% of GAD + interneurons ( Hof et al, 1999 ; Keller et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…In the disease conditions, CX3CR1 is downregulated in microglia [37]. [39,43] Immunohistochemistry [44] CCR2 Flow cytometry…”
Section: Markermentioning
confidence: 99%
“…Synaptic phagocytosis has also been observed after Toxoplasma infections. Carrillo et al showed that hippocampal microglia and infiltrating monocytes in a mouse model of Toxoplasma infection stripped and phagocytosed inhibitory presynaptic terminals around the cell body [44]. Using CX3CR1-GFP mice, in which both microglia and circulating monocytes express GFP, the authors found that there was a mixture of cells with high and low GFP fluorescence intensity in the brain parenchyma.…”
Section: Synapsesmentioning
confidence: 99%